Concepts of Improvement of the Scientific Aspect of the Universe in the System of Continuous Education - Berdiev U. B; Chorshanbieva N.A (Genius Journals, 2022)
The article covers the issues of providing students with a unified scientific view of the universe in general secondary schools. Natural sciences physics, chemistry, biology, geography were considered together and a single scientific view of the universe was interpreted.
Keywords: Nature; physics; chemistry; biology